The dynamic state of heat shock proteins in chicken embryo fibroblasts (The Rockefeller University Press, 1986)
Subcellular fractionation and immunofluorescence microscopy have been used to study the intracellular distributions of the major heat shock proteins, hsp 89, hsp 70, and hsp 24, in chicken embryo fibroblasts stressed by heat shock, allowed to recover and then restressed. Hsp 89 was localized primarily to the cytoplasm except during the restress when a portion of this protein concentrated in the nuclear region. Under all conditions, hsp 89 was readily extracted from cells by detergent. During stress and restress, significant amounts of hsp 70 moved to the nucleus and became resistant to detergent extraction. Some of this hsp 70 was released from the insoluble form in an ATP-dependent reaction. Hsp 24 was confined to the cytoplasm and, during restress, aggregated to detergent-insoluble perinuclear phase-dense granules. These granules dissociated during recovery and hsp 24 could be solubilized by detergent. The nuclear hsps reappeared in the cytoplasm in cells allowed to recover at normal temperatures. Sodium arsenite also induces hsps and their distributions were similar to that observed after a heat shock, except for hsp 89, which remained cytoplasmic. We also examined by immunofluorescence the cytoskeletal systems of chicken embryo fibroblasts subjected to heat shock and found no gross morphological changes in cytoplasmic microfilaments or microtubules. However, the intermediate filament network was very sensitive and collapsed around the nucleus very shortly after a heat shock. The normal intermediate filament morphology reformed when cells were allowed to recover from the stress. Inclusion of actinomycin D during the heat shock--a condition that prevents synthesis of the hsps--did not affect the intermediate filament collapse, but recovery of the normal morphology did not occur. We suggest that an hsp(s) may aid in the formation of the intermediate filament network after stress.